2002
DOI: 10.1097/00024382-200201000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of In vivo Infusion of Granulocyte Colony-Stimulating Factor on Immune Function

Abstract: As the applications of hematopoietic growth factors increase, their complex impact on host defense and immune responses continues to unfold. The effect of the administration of granulocyte colony-stimulating factor (G-CSF) on bacterial defense, proliferation of lymphocytes, and cytokine production by lymphocytes and peripheral blood mononuclear cells (PBMC) was studied. The effect of G-CSF administration on the phenotype of the cells in the major hematopoietic organs was studied as well. ACI rats were given 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Thus the salutary effects of estradiol administration on organ function after trauma-hemorrhage are mediated in part via upregulation of HO-1 expression and activity. hemorrhagic shock; heme oxygenase-1; chromium mesoporphyrin; liver; heart IT IS WELL ESTABLISHED THAT shock decreases organ perfusion and depresses organ as well as immune functions (2,9,12,32,38,42). There is also a growing body of evidence that indicates that heme degradation products [i.e., carbon monoxide (CO), biliverdin, bilirubin] may counteract the detrimental consequences of decreased organ perfusion and ischemia-reperfusion-related injury (1, 27) following low-flow conditions.…”
mentioning
confidence: 99%
“…Thus the salutary effects of estradiol administration on organ function after trauma-hemorrhage are mediated in part via upregulation of HO-1 expression and activity. hemorrhagic shock; heme oxygenase-1; chromium mesoporphyrin; liver; heart IT IS WELL ESTABLISHED THAT shock decreases organ perfusion and depresses organ as well as immune functions (2,9,12,32,38,42). There is also a growing body of evidence that indicates that heme degradation products [i.e., carbon monoxide (CO), biliverdin, bilirubin] may counteract the detrimental consequences of decreased organ perfusion and ischemia-reperfusion-related injury (1, 27) following low-flow conditions.…”
mentioning
confidence: 99%
“…As a rule, chemotherapy was administered every 3 weeks. After the completion of one course of chemotherapy, the next course of chemotherapy was administered after confirmation of the recovery of the white blood R 5 To whom correspondence should be addressed. E-mail: s30saito@ms.toyama-mpu.ac.jp cell, granulocyte, and platelet counts to 3000/mm 3 or greater, 1500/mm 3 or greater, and 10×10 4 /mm 3 or greater, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that CSFs not only increase granulocyte counts, but also modify immunological functions: G-CSF decreases the natural killer (NK) cell count in the peripheral blood mononuclear cells (PBMCs) 1) and NK cell activity, 2,3) and drives T cell polarization toward a T-helper cell 2 (Th2) phenotype. [4][5][6][7][8][9] Whereas these actions decrease graft-versus-host disease (GVHD) associated with hematopoietic stem cell transplantation, they may worsen the long-term prognosis of leukemia by lessening the graft-versus-leukemia (GVL) effect. GM-CSF has been reported to inhibit the decrease in NK and lymphokine-activated killer (LAK) activity caused by chemotherapy for solid cancers.…”
mentioning
confidence: 99%
“…Hematological support with granulocyte-colonystimulating factor (G-CSF), either natural or pegylated, was demonstrated to reduce the duration and severity of CTinduced neutropenia and thus infectious complications and hospitalizations. G-CSF also has an impact on the immune system; it has been shown to influence cytokine production and to modify T-and B-lymphocyte subsets [49][50][51].…”
Section: Lymphocyte Depletion and Recovery Following Antineoplastic Tmentioning
confidence: 99%